Early electrocardiographic indices for predicting chronic doxorubicin-induced cardiotoxicity. Issue 4 (April 2021) - Kinoshita, Toshio; Yuzawa, Hitomi; Natori, Kazuhiko; Wada, Ryo; Yao, Shintaro; Yano, Kensuke; Akitsu, Katsuya; Koike, Hideki; Shinohara, Masaya; Fujino, Tadashi; Shimada, Hideaki; Ikeda, Takanori
Highlights: Early detection of cancer therapeutics-related cardiac dysfunction (CTRCD) remains a significant problem. Electrocardiography (ECG) is the most realistic methodology in terms of cost-performance and invasiveness. Visual fluctuations of the ECG waveform were investigated in doxorubicin-cardiotoxicity. QTa prolongation and T-wave flattening may support early detection of CTRCD. Abstract: Background: Dealing with chemotherapy-related cardiac dysfunction (CTRCD) remains a significant problem complicated by the difficulty in early detection of cardiotoxicity. Electrocardiogram (ECG) is expected to be the most realistic methodology due to lower cost-performance and non-invasiveness. We investigated the long-term visual fluctuations in the ECG waveforms in patients with chronic doxorubicin (DOX)-induced cardiotoxicity to identify ECG indices for the early detection of cardiotoxicity. Methods: We conducted a retrospective case series study by reviewing the medical records of 470 consecutive patients with malignant lymphoma who were treated with DOX at our institute between January 2010 and December 2017. Of them, 23 (4.9%) patients developed left ventricular dysfunction and were diagnosed with CTRCD using echocardiography. We assessed the ECG indices on 12-lead ECG recordings before and after treatment in 15 patients; eight patients were excluded due to conduction disturbances or atrial fibrillation. Results: CTRCD was detected at a median of 475 (interquartile range, IQR: 341–1333) days after initiating chemotherapy. The evaluation of ECG indices preceding CTRCD development was performed 93 (IQR: 52–232) days before the detection of CTRCD. In the stage of CTRCD, the most significant ECG change was T-wave flattening in leads V3–V6 (12 patients, 80%). Additionally, QTa prolongation was observed in leads I and aVL (n = 10, 66%), leads II, III, and aVF (n = 9, 60%), and leads V3–V6 (n = 10, 73%). These ECG changes were not observed before the treatment but were detected mildly in the pre-CTRCD stage, which subsequently worsened in the CTRCD stage. Conclusions: This study indicated that T-wave changes and QTa prolongation may be useful as an early indicator before the onset of CTRCD in patients with DOX-induced cardiotoxicity.